The mediating role of self-efficacy in the relationship between self-management and health-promoting behaviors in post-PCI patients - Zhijie Cao; Ping Yan; Fang Hou; Xin Gu; Hu Peng; Lina Ma; Li Zhang (PLoS ONE, 2026)
Background Coronary artery disease (CAD) has become one of the most prevalent diseases worldwide. Self-management and self-efficacy are critical for enhancing healthy lifestyles in patients with postoperative CAD and are strongly associated with health-promoting behaviors. However, the underlying mechanisms of this association remain unclear. Purpose To explore the mediating role of self-efficacy between self-management and health-promoting behaviors in patients following percutaneous coronary intervention (PCI). Methods From November 2024 to March 2025, 400 post-PCI patients were selected by convenience sampling from a tertiary first-class hospital in Xinjiang. Surveys were administered using a general information questionnaire, a self-management scale, a self-efficacy scale, and a health-promoting lifestyle scale. Structural equation modelling was employed to investigate the pathways of action among the three variables. Results The scores for self-management behaviour, self-efficacy, and health-promoting lifestyle were (96.66 ± 10.11) scores, (44.49 ± 6.10) scores, and (162.91 ± 12.24) scores, respectively, with positive correlations between each pair of items. Self-efficacy partially mediated the relationship between self-management and health-promoting behaviors, with a standardized indirect effect of 0.317, accounting for 61.3% of the total effect. Conclusions Self-efficacy plays a partial mediating role between self-management and health-promoting behaviors. Healthcare professionals should pay attention to the self-efficacy of patients post-PCI to enhance their awareness of personal health and strengthen self-management, thereby promoting proactive adoption of healthy lifestyles.